Usborne Phonics Readers : Hen's Pens - Phil Roxbee Cox (London, United Kingdom Usborne Publishing Ltd, 2006)
Newly reissued to coincide with and support the Government's new focus on learning through synthetic phonics in primary schools, these delightful books will enthral, entertain and educate all young learners. They feature the ever-popular illustrations of Stephen Cartwright. They are developed in consultation with educational psychology expert, Dr. Marylynne Grant.
Keywords: PY - Language -- PY - Language